PENERAPAN MODEL SNOWBALL THROWING BERBANTUAN MEDIA VISUAL PADA MATA PELAJARAN IPS TERPADU SEBAGAI UPAYA PENINGKATAN MINAT DAN HASIL BELAJAR SISWA - Suriyanti, Yulia (Jurnal Pendidikan Ekonomi (JURKAMI), 2019)
Abstract: Â This research is motivated by the low interest and learning outcomes of class VIII students of SMP Negeri 8 Dedai. The approach used in this research is descriptive qualitative with the form of classroom action research. The research subjects were students of eight class Middle School. The research instruments used were questions about tests, observations, interviews, and documentation. The results of the study were obtained as follows: (1) the average value of the first cycle was 59 with classical completeness of 57% category less (2) the average value of the second cycle was 76.52 with 75% classical completeness in the very good category, (3 ) the average value of the third cycle is 89.28 with 100% classical completeness in the excellent category (4) the questionnaire results of students' interest shows the average questionnaire of the first cycle is 64.98% enough category, the second cycle has increased by 70.78% good category and in the third cycle learning interest reached 90.11%. Thus, it was concluded that the use of snowball throwing models assisted by visual media increased the interest and learning outcomes of eight class of Dedai Middle School.Â Keywords: Interest In Learning, Learning Outcomes, Snowball Throwing Models, Visual MediaÂ Abstrak: Penelitian ini dilatarbelakangi rendahnya minat dan hasil belajar siswa kelas VIII SMP Negeri 8 Dedaiâ€. Pendekatan yang digunakan dalam penelitian ini adalah kualitatif deskriptif dengan bentuk penelitian tindakan kelas (PTK). Subjek penelitian adalah siswa kelas VIII SMPN 8 Dedai. Instrumen penelitian yang digunakan adalah soal tes, observasi, wawancara, dan dokumentasi. Adapun hasil penelitian diperoleh sebagai berikut: (1) nilai rata-rata siklus I adalah 59 dengan ketuntasan klasikal 57% kategori kurang sekali (2) nilai rata-rata siklus II adalah 76,52 dengan ketuntasan klasikal 75% kategori amat baik, (3) nilai rata-rata siklus III adalah 89,28 dengan ketuntasan klasikal 100% kategori amat baik (4) hasil angket minat siswa menunjukan rata-rata angket siklus I adalah 64,98% kategori cukup, siklus II mengalami peningkatan sebesar 70,78% kategori baik dan pada siklus III minat belajar mencapai 90,11%. Dengan demikian, disimpulkan penggunaan model snowball throwing berbantuan media visual meningkatkan minat dan hasil belajar siswa kelas VIII SMPN 8 Dedai.Kata Kunci : Minat Belajar, Hasil Belajar, Model Snowball Throwing, Media Visual